Factors Influencing the Success of Teaching of Universitas Pgri Semarang Students in International PPL Program in Malaysia - ., Muhdi; Widodo, Suwarno; Buchori, Achmad; Ambarini, Ririn; Fadhila, Nur (International Journal of Engineering and Technology, 2018)
The rapid development of science and technology requires universities to prepare competent human resources in their fields, one of which is the ability in teaching practice in schools. To improve the students’ ability in teaching practice in both  Indonesia and overseas schools, it requires a strategic effort, such as exchange student program. Therefore, Universitas PGRI Semarang conducts MOU with Universiti Teknologi Malaysia and Institut Pendidikan Guru Malaysia. Through this program, the students are  expected to be able to adapt the character learning and  become a professional teacher in the future.Factors influencing the success of the students in joining the exchange program can be seen from the internal and external aspects. Therefore the purpose of this study is to determine what factors influence the success of teacher students of Universitas PGRI Semarang in Malaysia. The population of all students who joined the international PPL program in Malaysia is 18 students with random sampling for students teaching in grade 4 and 5. The data  were obtained from questionnaire and interview.Based on the questionnaire, it is found that 95% of Universitas PGRI Semarang students are very pleased to join the International PPL program in Malaysia, as the cultural environment similar to the Indonesian nation give the easier adaptation process. Based on the interview with the students, the benefits of this program are as follows: 1) 90 % of students claim to gain new life and social experiences; 2) 87 % of students get additional knowledge about education in Malaysia; 3) 92% of students get strong fraternity from other apprentice students of other state / private universities, and 4) only 30%  of students are constrained by the language difficulties, 30% of students have difficulties in learning time, and 20% of students have difficulties in funding.
Keywords: factors of succesful teaching practice; international PPL program.